2006
DOI: 10.1007/s00330-006-0368-1
|View full text |Cite
|
Sign up to set email alerts
|

Coronary vessel-wall and lumen imaging using radial k-space acquisition with MRI at 3 Tesla

Abstract: This study investigates the feasibility of imaging the coronary lumen and vessel-wall, using MRI with a radial k-space trajectory at 3 T. Such radial trajectories offer the advantage of greater vessel sharpness than traditional Cartesian trajectories. This field strength offers an increased signal-to-noise ratio (SNR) compared with 1.5 T, which compensates for the slight SNR reduction due to the radial sequence. Images of the coronary lumen were acquired for seven healthy volunteers. In ten volunteers the vess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 39 publications
(69 reference statements)
1
8
0
Order By: Relevance
“…These studies have been conducted using a variety of different pulse sequences including segmented gradient echo (GRE) sequences [55,57,58,60,61], fast spin echo sequences [62], and recently, SSFP sequences [63,64]. There have been two studies directly comparing non-contrast coronary angiography images acquired at 1.5 and 3.0T.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies have been conducted using a variety of different pulse sequences including segmented gradient echo (GRE) sequences [55,57,58,60,61], fast spin echo sequences [62], and recently, SSFP sequences [63,64]. There have been two studies directly comparing non-contrast coronary angiography images acquired at 1.5 and 3.0T.…”
Section: Resultsmentioning
confidence: 99%
“…To implement SSFP sequences at 3.0T, flip angles must be adjusted and/or repetition times increased. Obtaining consistent results when imaging the coronary arteries using SSFP sequences have proved difficult at 3.0T due to the high sensitivity of SSFP to off-resonance artifacts, and it has been suggested that better image quality may be obtained more consistently by using a spoiled GRE sequence instead of SSFP [60,61]. …”
Section: Resultsmentioning
confidence: 99%
“…Several approaches are likely needed in combination to improve image quality and SNR in order to make this a more robust and reliable technique. These include optimized multi-element surface coils, 3 D acquisition[10,23], free-breathing methods to allow longer acquisitions[26], radial k -space sampling[27], and higher magnetic field strength, such as 3T[28-31]. …”
Section: Discussionmentioning
confidence: 99%
“…In a study of patients with CAD, a free-breathing, navigator-gated technique for 3D coronary black blood imaging showed increased coronary vessel wall thickness in patients with mild CAD when compared to a healthy control population [53]. Preliminary studies of coronary vessel wall imaging at 3 T are promising and show the potential to detect preclinical disease and monitor treatment effects over time [52, 54]. …”
Section: Coronary Vessel Wall Imagingmentioning
confidence: 99%